The world of Edena - Moebius, 1938-2012 (Moebius library, 2016)
"Stel and Atan are interstellar repairmen searching for a lost space station and its crew. Their journey takes them to the mythical paradise planet Edena where they unwittingly and unwillingly join a multidimensional battle between good and evil"--